Prevalence of otorhinolaryngologic diagnoses in the pediatric emergency room - Signorelli, Luiz Gabriel (International Archives of Otorhinolaryngology, 2013)
Introduction: Fever and pain, which are very common in ear, nose, and throat pathologies, are among the most frequent complaints recorded during emergency room pediatric patient treatment. Most of time, the pediatricians are called on to evaluate otorhinolaryngology disorders that requires specialist assessment. Aim: To determine the prevalence of otorhinolaryngologic diagnoses in a pediatric population in a reference hospital in the city of Itatiba, São Paulo. Methods: We evaluated 2,054 pediatric patients (age range, 0-12 years, 11 months) in this descriptive, transversal observational (survey) study. Data collection was performed by a single observer during 103 night shifts (07:00 p.m. to 07:00 a.m.) between January and December 2011, and included documentation of the main diagnosis, and patient age and sex. The ethics committee and research institution approved study. Patients were divided into 2 groups based on diagnosis: Group A otorhinolaryngology disease and Group B included diagnoses not contained in Group A. Results: Of the total enrolled patients, 52.2% corresponded to Group A and 47.8% to Group B; 51.9% were male and 48.1% were female. The average age was 4.5 years (Group A, 3.93 years; Group B, 5.03 years). We compared the prevalence of the diagnostic hypotheses of the 2 groups. Conclusion: A large number of patients sought treatment at pediatric emergency rooms for otorhinolaryngologic diagnoses.